1994
DOI: 10.1007/bf00175245
|View full text |Cite
|
Sign up to set email alerts
|

The 13C Chemical-Shift Index: A simple method for the identification of protein secondary structure using 13C chemical-shift data

Abstract: A simple technique for identifying protein secondary structures through the analysis of backbone 13C chemical shifts is described. It is based on the Chemical-Shift Index [Wishart et al. (1992) Biochemistry, 31, 1647-1651] which was originally developed for the analysis of 1H(alpha) chemical shifts. By extending the Chemical-Shift Index to include 13C(alpha), 13C(beta) and carbonyl 13C chemical shifts, it is now possible to use four independent chemical-shift measurements to identify and locate protein seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

85
1,673
0
8

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,031 publications
(1,776 citation statements)
references
References 35 publications
85
1,673
0
8
Order By: Relevance
“…16 We thus compared the H-D exchange of backbone NHs between WT and Y9P I27 domains. We first confirmed that NMR chemical shift indexes that reflect secondary structures 17 were similar for WT and Y9P I27 domains [ Fig. 3(A)], as suggested by their similar CD spectra [ Fig.…”
Section: Resultssupporting
confidence: 59%
“…16 We thus compared the H-D exchange of backbone NHs between WT and Y9P I27 domains. We first confirmed that NMR chemical shift indexes that reflect secondary structures 17 were similar for WT and Y9P I27 domains [ Fig. 3(A)], as suggested by their similar CD spectra [ Fig.…”
Section: Resultssupporting
confidence: 59%
“…The NOE experiments were carried out with a relaxation delay of 4.4 s, which is 4^6 times the 15 N T 1 values. The secondary structure was assigned using the chemical shift index (CK and HK) [15,16] and the sequential NH(i)3NH(i+1) and CKH(i)3CKH(i+3, 4) NOEs.…”
Section: Methodsmentioning
confidence: 99%
“…The NOEs were used along with Ca chemical shifts and 3 J HNHA scalar coupling values from the isotropic soft HNCA-E-COSY experiment to identify secondary structure types. 28 To aid in structure determination, a set of short range and long range interresidue NOEs was identified and treated more quantitatively. Peak intensities were compared separately with average intensities of HAÀ ÀHN and HNÀ ÀHN peaks from regions known to be in well defined a-helices and classed based on intensities being the same or stronger than the HNÀ ÀHN standard (strong), the same as the HNÀ ÀHA standard (medium) or weaker than either (weak).…”
Section: Nmr Data Processing and Analysismentioning
confidence: 99%